(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The rapid evolution of industrial automation has underscored the necessity for smarter, faster, and more adaptable systems. Packaging robot manipulators play a crucial role in enhancing production efficiency. This research investigates the application of artificial intelligence (AI) algorithms to optimize the operations of packaging robots. Specifically, the study focuses on trajectory planning, real-time object detection, and system adaptability. Key findings include a significant reduction in execution time and energy consumption while maintaining high precision levels. The results validate the integration of AI as a transformative approach in robotic packaging systems.